The effect of aluminum and germanium oxides on the crystallization process and magnetic properties of Li2O–Fe2O3–SiO2 glass system. Issue 1 (January 2015) - Salman, S.M.; Salama, S.N.; Abo-Mosallam, H.A.
Abstract: The crystallization behavior of Li2 O–Fe2 O3 –SiO2 glasses containing Al2 O3 and GeO2 has been studied using differential thermal analysis (DTA), X-ray diffraction (XRD) and scanning electron microscopy (SEM). The crystalline phases identified by XRD were lithium metasilicate (Li2 SiO3 ), Li-aegirine (LiFeSi2 O6 ), lithium ferrite (LiFe5 O8 ), and varieties of β-quartz solid solution. The partial swap of Al2 O3 instead of SiO2 has led to the formation and growth of β-quartz solid solution with formula LiAlSi2 O6 . However LiFe5 O8 phase has been formed instead of LiFeSi2 O6 . In the case of GeO2 /SiO2 replacement β-quartz ss has the preferential tendency to accommodate GeO2 in its structure to form different formulas of LiAl(Si x, Ge1− x )2 O6 phases. The magnetic property of the prepared glass-ceramics was characterized using a vibrating sample magnetometer (VSM). The evolutions of magnetic parameters in the crystallized glasses were greatly dependent on the amount and size of iron containing phases present in the material. The coercive force and remnant of the glass-ceramic materials have increased by decreasing the size of iron magnetic phase. Under applied magnetic field of ±20 kOe, the saturation magnetization ( M s ), remanance magnetization ( M r ), and coercivity ( H c ) varied from 0.46 to 0.83 emu/g, 0.056 to 0.16 emu/g and 118 to 204 G, respectively. The high coercivity values of the prepared glass-ceramics are expected to be useful as permanent magnets.